2017
DOI: 10.1007/s10157-017-1432-7
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump versus on-pump coronary surgery in patients with chronic kidney disease: a meta-analysis

Abstract: Compared with ONCAB, OPCAB is associated with superior postoperative morbidity and the early mortality in CKD patients. Long-term survival is comparable between the two surgical revascularizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
2
17
0
2
Order By: Relevance
“…Wang and colleagues found that there was no difference between off-pump and on-pump regarding early mortality, which run in line with our results [21]. Deppe and colleagues found that there was no difference between off-pump and on-pump groups regarding the 30 days mortality rate [14].…”
Section: Discussionsupporting
confidence: 90%
“…Wang and colleagues found that there was no difference between off-pump and on-pump regarding early mortality, which run in line with our results [21]. Deppe and colleagues found that there was no difference between off-pump and on-pump groups regarding the 30 days mortality rate [14].…”
Section: Discussionsupporting
confidence: 90%
“…A meta‐analysis including 17 studies with 201 889 patients with chronic kidney disease associated OPCAB with lower early mortality (OR: 0.88; 95% CI, 0.82–0.93; P <0.0001) and morbidity compared with ONCAB. However, there was no difference regarding long‐term survival (HR: 1.08; 95% CI, 0.86–1.36; P =0.51) 75. A large study based on the National Health Research Institute of Taiwan reported similar outcomes of OPCAB and ONCAB in patients on dialysis 76.…”
Section: Opcab In Specific Subsets Of Patientsmentioning
confidence: 93%
“…1 With the advent of cardiac stabilizers that allowed for technical improvements and the realization that specific patient populations benefit from coronary revascularization without the use of CPB, the indications for OPCAB have been expanded to include higher-risk patient populations, including those with end-stage renal disease. 18,19 These include the extreme elderly, females, and patients with severe carotid or aortic atherosclerotic disease. In patients with severe end-organ dysfunction or failure, particularly renal disease and cirrhosis, OPCAB has been shown to reduce morbidity and mortality compared with on-pump bypass techniques.…”
Section: Patient Selectionmentioning
confidence: 99%